2021
DOI: 10.3390/ijms22094361
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Current Stimulation Has Potential Effects of Hair Growth-Promotion on Human Hair Follicle-Derived Papilla Cells and Animal Model

Abstract: Recently, a variety of safe and effective non-pharmacological methods have been introduced as new treatments of alopecia. Micro-current electrical stimulation (MCS) is one of them. It is generally known to facilitate cell proliferation and differentiation and promote cell migration and ATP synthesis. This study aimed to investigate the hair growth-promoting effect of MCS on human hair follicle-derived papilla cells (HFDPC) and a telogenic mice model. We examined changes in cell proliferation, migration, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…We have conducted various skin-related studies such as wound healing, hair growth promotion, and skin improvement through previous studies [ 17 , 46 , 47 ]. Consistent with other studies, it has been shown to have positive effects on the skin within the intensity range below 200 µA.…”
Section: Discussionmentioning
confidence: 99%
“…We have conducted various skin-related studies such as wound healing, hair growth promotion, and skin improvement through previous studies [ 17 , 46 , 47 ]. Consistent with other studies, it has been shown to have positive effects on the skin within the intensity range below 200 µA.…”
Section: Discussionmentioning
confidence: 99%
“…Topical medications have favorable side effects compared to those of systemic therapies, but many topical medicines are poorly absorbed transdermally, limiting their effective concentration at HFs and targeting dermal HFs. Other approaches, including prostaglandin F2 α (PGF2 α ) analogs, Janus kinase (JAK) inhibitors, cytokine inhibitors [ 5 ], laser therapy [ 6 ], and microcurrent stimulation [ 7 ] still lack clinical trials that are evidence-based and at a high level to affirm their efficacy. Therefore, the available treatments are far from desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it is suggested that modulating the cell cycle is an efficient strategy to reduce lipid accumulation in the multi-clonal expansion (MCE) period [ 38 , 39 ]. We have reported in previous studies that MCS contributed to the cell cycle progression of HFDPC cells at 25 μA and 50 μA concentrations for hair growth [ 40 ]. However, further studies are needed regarding whether MCS affects adipose cell cycle-related proteins.…”
Section: Discussionmentioning
confidence: 99%